Seasonal and vertical tidal variability in the Southeastern Mediterranean Sea - Mantel, Nadav; Feliks, Yizhak; Gildor, Hezi; Poulain, Pierre-Marie; Mauri, Elena; Menna, Milena (Frontiers in Marine Science, 2024)
Currents and pressure records from the DeepLev mooring station and drifter data in the eastern Levantine Basin were analyzed to identify the dominant tidal constituents and their seasonal and depth variability. Harmonic and spectral analysis of seasonal segments of currents and pressure reveal key attributes of the tidal regime: (1) dominant semidiurnal sea level variability; (2) seasonal variation of semidiurnal and diurnal tides in both currents and pressure datasets; and (3) significant diurnal currents with weak semidiurnal currents across all seasons. The most dominant tidal constituent from the pressure dataset is the M2 (12.4 h). Results from pressure datasets align with previous models and observations of semidiurnal tides. In contrast, the diurnal tides are larger than previously reported by 8-9 cm in the winter and 1-2 cm in the summer. The surface current tidal regime differs from prior reports in the eastern Levantine Basin, with M2 magnitudes weaker by 1 cm s -1 , while the diurnal tides (K1, O1) are 1-2 cm s -1 larger. Seasonal segments showed seasonal differences in the local tidal regime's amplitudes. The most pronounced seasonal differences were with the K1 and S2 tides, with differences between winter and fall of 7 cm for the K1 and 4 cm between summer and fall for the S2. We utilized the DeepLev datasets to compare a moored device with surface drifters near DeepLev by analyzing the M2 and S2 tides. Additionally, we examined data at different dataset lengths, considering the time constraints needed to resolve the tides adequately. Longer datasets improved the resolution of the tidal analysis and reduced amplitude leakages from nearby frequencies, resulting in a more realistic and accurate analysis of the tidal currents. Conversely, longer datasets resulted in fewer drifters remaining our study region for the allotted dataset length. From 32 available segments in 15 day dataset to 7 with a 30 day dataset, reducing the effectiveness of drifters as a local tidal research tool.